Analisis Defisensi Kesehatan Komunitas Pada Kelompok Hipertensi - Putri, Lydia Mardison; Tanjung, Ruqowiyah (REAL in Nursing Journal, 2021)
Background: Community health deficiencies are a refusing health condition in a community. One of them is increasing chronic blood pressure in the long term (140/90 mmhg). Pakan Kamis Community Health Center had the highest hypertension data. There were 3796 cases found in 2017 and in Jorong Sonsang 49 people did not eat regular medication (98.1%). Therefore, hypertension is a healthy Indonesia Program with a family approach since 2017. This study aimed to determine An Analysis of Community Health Deficiency in Hypertension Groups in Pakan Kamis Community Health Center. Methods: The research was qualitative research with the phenomenology approach. It was conducted in Pakan Kamis Community Health Center on December to January 2019. Purposive Sampling had been used to choose the samples. The informants were 30 health workers (9 people and 21 people with hypertension groups). The data were collected through depth interviews, observation and document review. Then, it was processed and analyzed by using Huberman. The data had been reduced, presented, drawn the conclusions and also explained in narrative form. The technique of checking the validity of qualitative data by using a credibility test was by source triangulation. Result: The research results are obtained from the input aspects of performance barriers, management function processes, genetic processes, behavior, lifestyle, environment, family support. Conclusion: it can be concluded that community health efficiency was caused by several factors. It is expected that the Head of the Community Health Center and the program holder to improve their existing human resources.Keywords: Community Health Deficiencies, Hypertension